Christianity, Good Health and Vegetarianism in Japan, c. 1900-45 - Fujimoto, Hiro (Food & History, 2022)
Abstract Western food cultures have been popular in Japan since the middle of the nineteenth century. Although meat-based diets spread quickly among the Japanese population at the turn of the twentieth century, some Japanese groups, particularly socialists and Seventh Day Adventists, were attracted to Western vegetarianism. Both socialists and Adventists enthusiastically discussed the significance of vegetarianism, but socialists soon lost interest. In contrast, Japanese Adventists have continued to follow meatless diets, and the Japanese Seventh Day Adventist Church remains one of the leading promoters of vegetarianism in Japan. However, food historians have paid little attention to their role in spreading vegetarianism in Japan. This article examines how Japanese Adventists adopted and developed meatless diets, comparing their approach to both socialist vegetarianism in Japan and Adventist vegetarianism in the United States. Abstract Les cultures alimentaires occidentales sont populaires au Japon depuis le milieu du XIXe siècle. Bien que les régimes à base de viande se soient rapidement répandus parmi la population japonaise au début du XXe siècle, certains groupes japonais, notamment les socialistes et les membres de l’Église adventiste du septième jour, ont été attirés par le végétarisme occidental. Les socialistes et les adventistes ont discuté avec enthousiasme de l’importance du végétarisme, mais les socialistes ont rapidement perdu leur intérêt. En revanche, les adventistes japonais ont continué à suivre des régimes sans viande, et l’Église adventiste du septième jour japonaise reste l’un des principaux promoteurs du végétarisme au Japon. Cependant, les historiens de l’alimentation ont accordé peu d’attention à leur rôle dans la diffusion du végétarisme au Japon. Cet article examine comment les adventistes japonais ont adopté et développé les régimes sans viande, en comparant leur approche au végétarisme socialiste au Japon et au végétarisme adventiste aux États-Unis.